Imaging diagnosis of Cystic Endometrial Hyperplasia Complex – Pyometra (CHEC–P): Case report (Research, Society and Development, 2021)
The Cystic Endometrial Hyperplasia – Pyometra complex (CHEC–P) is widely found in the daily life of the medical clinic of small animals, being the main disease of the female reproductive tract. Thus, the rapid diagnosis of the disease is necessary, so that the best treatment for the female can be established, with the main diagnostic method being the identification by ultrasound image. A 9-year-old, uncastrated poodle dog was taken by her tutor to a veterinary clinic in Porto Velho, Rondônia. The bitch had apathy and depression and on physical examination the bitch showed distended abdomen and pain on abdominal palpation. During a conversation, the tutor reported giving birth control to the bitch for several years, which made the veterinarian suspect the beginning of a possible pyometra. With that, the veterinarian ordered an abdominal ultrasound. After performing the ultrasound, Cystic Endometrial Hyperplasia–Pyometra (HEC¬–P) was found, as well as splenomegaly. The treatment used was ovariohysterectomy (OH). The patient recovered well, was discharged a few days after surgery and returned to check her clinical status and remove the stitches. It was concluded that the clinician's perception and the use of ultrasound diagnosis were of paramount importance for the conclusion of the case.